#TITLE_ALTERNATIVE# - ABDILLAH (NIM : 15108020) ; Pembimbing I : Prof.Dr.Ir. Hasanuddin Z. Abidin, M.Sc ; Pembimbing, RIDHO
Land subsidence monitoring which is to identify major changes in height of land in the Bandung Basin has many period doing with GPS technology, of which since 2000. In addition to using GPS technology, there is many methods for monitoring land subsidence, one of each is Geometric-Historical Method. This method involves measuring instances of land subsidence with measuring tape for geometric data and obtaining information on the first occurrences of the pheonomena for historical data. Through the thesis, data collection with Historical and Geometrical Method conducted in Bandung Basin, data will then be compared with GPS observational data from 2000 to 2012. This method can provides monitoring data on the largest average values of land subsidence annualy, namely in Dayeuhkolot 14,7 cm, Cimahi 13,1 cm, Gedebage 12,5 cm, Rancaekek 9,2 cm, Bojongsoang 6,7 cm, Balendah 7,5 cm, Solokan Jeruk 5,3 cm, and Sapan 5,0 cm annually. Compared with the results of the GPS, then there is an average difference for each area of 4,5 cm, 1,0 cm, 4,7 cm, 5,0 cm, 0,2 cm, 0,9 cm, 1,7 cm, and 2,0 cm.